Spatio-temporal analysis of potential aquifer recharge: Application to the Basin of Mexico - Carrera-Hernández, J.J.; Gaskin, S.J. (Journal of hydrology (Amsterdam), 2008)
Regional estimates of aquifer recharge are needed in data-scarce regions such as the Basin of Mexico, where nearly 20 million people are located and where the Basin’s aquifer system represents the main water source. In order to develop the spatio-temporal estimates of aquifer recharge and to analyze to what extent urban growth has affected aquifer recharge, this work presents a daily soil water balance which uses different vegetation and soil types as well as the effect of topography on climatological variables and evapotranspiration. The soil water balance was applied on a daily time step in the Basin of Mexico for the period 1975–1986, obtaining an annually-lumped potential recharge flow of 10.9–23.8 m 3/s (35.9–78.1 mm) in the entire Basin, while the monthly values for the year with the largest lumped recharge value (1981 = 78.1 mm) range from 1 m 3/s (0.3 mm) in December to 87.9 m 3/s (23.7 mm) in June. As aquifer recharge in the Basin mainly occurs by subsurface flow from its enclosing mountains as Mountain Block Recharge, urban growth has had a minimal impact on aquifer recharge, although it has diminished recharge in the alluvial plain.